Transitioning to community-based mental health service delivery: opportunities for Ukraine. Issue 1 (1st January 2020) - Quirke, Eleanor; Suvalo, Orest; Sukhovii, Oleksii; Zöllner, York
ABSTRACT: Background and objectives : Ukraine's mental health system has been found to be inadequate and unresponsive to the needs of the population, in view of its emphasis on inpatient service delivery. This study sought to identify potential changes to the organization and financing of mental health services within the Ukrainian health system that would facilitate the delivery of mental health services in a community-based setting. Methodology : A systematic literature review was undertaken to identify organizational and financing features that have been successfully used to enable and incentivize the delivery of community-based mental health services in Central or Eastern European and/or former Soviet Union countries. Results : There was limited literature on the organizational and financing features that facilitate the delivery of community-based care. Key facilitators for transitioning from institution-based to community-based mental health service delivery include; a clear vision for community-based care, investment in the mental health system, and mechanisms that allow health funding to follow the patient through the health system. Conclusions : Ukraine should adopt strategic purchasing mechanisms to address inefficiency in the financing of its mental health system, and prioritize collaborative planning and delivery of mental health services. Ongoing reform of the Ukrainian health system provides momentum for instituting such changes.